Alternative culture media for fungal growth using different formulation of plant material - SHIPRA JHA; S.N DIKSHIT (International Journal of Pharma and Bio Sciences, 2017)
Keeping in view the cost of the yeast extract as well as difficulty in its procurement in remote places, suitable alternative to such conventional media components needs to be explored in order to facilitate the applicability of the treatment process in remote small- scale units. Habitat conditions such as nutrient availability, temperature, humidity, etc greatly affect the growth of microorganisms, decreasing their activity and field viability. Due to several practical difficulties, such a biological system may not be feasible for effluent treatment in remote rural industries. Hence, for evolving a viable biological system, a suitable formulation of efficient strain would form an important input for the effluent treatment plant. This study describes the development of three A.lentulus formulations using organic bases as rice based fungal formulation (RBFF), wheat based fungal formulation (WBFF) and maize based fungal formulation (MBFF)which could function both as nutrition as well as a carrier. All three formulations were evaluated in terms of shelf life and metal removal efficiency at definite intervals. Based on the findings of this study, it is observed that the development and evaluation of the shelf life of three formulations formulations i.e rice based fungal formulation, maize based fungal formulation and wheat based fungal formulation performed well in controlled conditions i.e 300C & 40C upto seven months.